Rheumatologists' insight into medication adherence in patients with rheumatoid arthritis: A qualitative study. (19th July 2019) - Heidari, Parvaneh; Cross, Wendy; Weller, Carolina; Team, Victoria; Nazarinia, Mohammadali; Crawford, Kimberley
Abstract: Background: Medication non‐adherence is prevalent among patients with rheumatoid arthritis (RA). Rheumatologists are specialists in medication prescribing and counselling for RA, but their insights regarding medication adherence have not been studied. Objective: To explore rheumatologists' insights into medication adherence in patients with RA. Methods: A qualitative study using semi‐structured interviews with 10 rheumatologists in Iran was undertaken. Thematic analysis was conducted to identify how rheumatologists assess medication adherence and their perceived determinants of adherence. The identified determinants of adherence were mapped according to the Andersen's Behavioral Model of Health Service Use. Results: Six participants were male, and the mean age was 47 years. The mean years of experience as a rheumatologist was 8.6 (SD = 7.1) years. Rheumatologists did not use a validated tool for medication adherence assessment. They assessed medication adherence either by asking their patients simple questions or using laboratory test results. The identified determinants of adherence were divided into 3 groups: patient‐, rheumatologist‐ and healthcare organization‐related determinants. The proposed suggestions to improve adherence were: (a) to understand a patient's financial situation before prescribing more expensive medications; (b) to employ a dose‐reducing strategy; (c) to give hope to patients regarding remission; and (d) to arrange a session with the nurse educator. Conclusion: The findings of this study provide insight into rheumatologists' perspectives on medication adherence of patients with RA. The identified determinants of adherence could be considered when developing initiatives to improve medication adherence in this group of patients.